Microbial and Antibiotic Resistant E. coli Contamination in Retail Eggs Produced by Alternative and Conventional Rearing Methods - Guran, HS; Esen, S; Alali, W (Journal of the Hellenic Veterinary Medical Society, 2023)
The aims of this study were to determine: i) the presence of total mesophilic aerobic bacteria (TMAB), total psychrophilic aerobic bacteria (TPAB) coliform, E. coli, Enterobacteriaceae and Salmonella in retail eggs produced in different poultry rearing systems, ii) Enterobacteriaceae species diversity, and iii) antibiotic resistance profile of E. coli isolates. A total of 350 retail eggs produced by four different rearing systems [organic (n= 100), free-range (n= 100), barn (n= 50) and conventional-cage (n=100)] were collected and characterized microbiologically. Out of the 350 eggs tested, the eggshell surface samples were contaminated, with TMAB, TPAB, coliform, E. coli and Enterobacteriaceae at positive percentages of 100%, 100%, 49.1%, 18.6% and 38%, respectively. The positive percentage of coliform, E. coli and Enterobacteriaceae were statistically significant between rearing systems (P<0.05). However, only mean numbers of TMAB were statistically significant between rearing systems (P<0.05). The contamination percent positive crushed eggshell samples, with TMAB, TPAB, coliform, E. coli and Enterobacteriaceae were 100%, 100%, 50%, 33.7% and 42.5%, respectively. Salmonella was detected from only one Enterobacteriaceae isolate obtained from an organic eggshell pool but not from eggshell surfaces or egg yolks. A total of 35 E. coli isolates were recovered from Enterobacteriaceae isolates. Twelve (34.3%) of them exhibited resistance to least one antibiotic tested. The dominant type of resistance was to ampicillin detected in all 12 E. coli isolates. This study provides valuable baseline data of the occurrence of species diversity of Enterobacteriaceae and antibiotic resistant E. coli in retail eggs produced by alternative or conventional-caged rearing methods which can be used for future risk assessments.